Trace Element Signatures in Pyrite and Marcasite From Shallow Marine Island Arc-Related Hydrothermal Vents, Calypso Vents, New Zealand, and Paleochori Bay, Greece - Nestmeyer, Mark; Keith, Manuel; Haase, Karsten M.; Klemd, Reiner; Voudouris, Panagiotis; Schwarz-Schampera, Ulrich; Strauss, Harald; Kati, Marianna; Magganas, Andreas (Frontiers in Earth Science, 2021)
Fluid conditions of shallow marine hydrothermal vent sites (<200 mbsl) in island arcs resemble those of subaerial epithermal systems. This leads to a distinct mineralisation-style compared to deeper arc/back-arc (>200 mbsl) and mid-ocean ridge-related environments (>2000 mbsl). At Calypso Vents in the Bay of Plenty and Paleochori Bay at the coast of Milos Island, fluids with temperatures <200°C are emitted through volcaniclastic sediments in water depths <200 mbsl. The hydrothermal mineralisation from these fluids is dominated by pyrite and marcasite showing diverse textures, including colloform alternations, semi-massive occurrences surrounding detrital grains, vein-type pyrite, and disseminated fine-grained assemblages. Pyrite and marcasite from Calypso SE show elevated concentrations of volatile elements (e.g., As, Sb, Tl, Hg) implying a vapour-rich fluid phase. By contrast, elements like Zn, Ag, and Pb are enriched in hydrothermal pyrite and marcasite from Calypso SW, indicating a high-Cl liquid-dominated fluid discharge. Hence, vapour-liquid element fractionation induced by fluid boiling is preserved in the seafloor mineralisation at Calypso Vents. Hydrothermal mineralisation at very shallow vent sites (<10 mbsl), like Paleochori Bay, are affected by wave action causing a seasonal migration of the seawater-fluid interface in the sediment cover. The δ34S composition of native S crusts and crystalline S (0.7 to 6.7 ‰) is indicative for host rock leaching and thermochemical reduction of seawater sulphate. By contrast, the highly negative δ34S signature of native S globules in sediments (-7.6 to -9.1 ‰) is related to microbial sulphate reduction or a subordinate magmatic fluid influx. Alunite-jarosite alteration (Paleochori Bay) and a mineral assemblage consisting of orpiment, realgar, and native S (Calypso Vents) may also suggest a contribution by an oxidised (sulphate-rich) low pH fluid of potential magmatic origin. However, fluid boiling is pervasive at Calypso Vents and Paleochori Bay, and the condensation of vapour-rich fluids in a steam-heated environment may produce a similar alteration and mineralisation assemblage without a significant magmatic fluid influx, as known from some subaerial epithermal systems.